2021
DOI: 10.1002/ajoc.202100508
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Clock Catalytic System: Highly Efficient and Self‐Indicating Synthesis of Benzoheterocycles at Ambient Temperature

Abstract: Inspired by the mechanism of the clock reaction, we rationally constructed a novel phosphomolybdenum blue (PMB) clock catalytic system for a highly efficient synthesis of benzimidazoles and benzothiazoles simply at ambient temperature. The current PMB clock catalytic system exhibits a sharp decoloration event to announce the depletion of the intermediateconstraint, making this synthetic approach selfindicating and TLC-free. 31 P NMR and XPS analysis of PMBcatalyst showed that only two Mo 6 + atoms are reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…According to the procedures established in benzimidzole synthesis, [ 35 ] the reaction of 1.0 equiv of o ‐aminobenzamide, 1.1 equiv of benzaldehyde, 1 mol% PMA, and 1.2 equiv of tert ‐butyl hydrogenperoxide (TBHP) was conducted in DMSO at ambient temperature. TLC monitoring indicated that it involves two phases, which is very similar to what happens in benzimidazole synthesis.…”
Section: Results and Disscussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the procedures established in benzimidzole synthesis, [ 35 ] the reaction of 1.0 equiv of o ‐aminobenzamide, 1.1 equiv of benzaldehyde, 1 mol% PMA, and 1.2 equiv of tert ‐butyl hydrogenperoxide (TBHP) was conducted in DMSO at ambient temperature. TLC monitoring indicated that it involves two phases, which is very similar to what happens in benzimidazole synthesis.…”
Section: Results and Disscussionmentioning
confidence: 99%
“…It is noteworthy that the sharp decoloration event of the PMB clock‐catalyzed benzimidazole/benzothiazole synthesis [ 35 ] was not observed in quinazolin‐4(3 H )‐one synthesis (Figure 1A). Originally, we ascribed the constant color to the fact that the reaction rate of oxidative dehydrogenation by PMA (Mo(VI) → Mo(V)) is relatively slow than that of the oxidation of PMB back to PMA by TBHP (Mo(V) → Mo(VI)).…”
Section: Results and Disscussionmentioning
confidence: 99%
See 1 more Smart Citation